Student-like models for risky asset with dependence. Issue 3 (4th May 2017) - Castelli, F.; Leonenko, N. N.; Shchestyuk, N.
ABSTRACT: We present a new construction of the Student and Student-like fractal activity time model for risky asset. The construction uses the diffusion processes and their superpositions and allows for specified exact Student or Student-like marginal distributions of the returns and for flexible and tractable dependence structure. The fractal activity time is asymptotically self-similar, which is a desired feature seen in practice.